Allowances, Job Commitment, Work Environment and Employees’ Attitude in Government Ministries in Ekiti State - Dada, Joseph Adegboye; Babatunde, Olayinka Funmi; Ige, Olusegun Micheal (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Employee attitude is essential for the efficiency and productivity of government institutions, as it influences the promptness, responsiveness, and quality of public service delivery. In the context of Ekiti State ministries, where challenges in motivating personnel persist, allowances and workplace conditions are seen as significant factors affecting job commitment and attitude. The study was conducted to examine the influence of allowances and work environment on employee attitude to work in government ministries in Ekiti State. Despite existing research on such factors globally and in parts of Nigeria, there is a scarcity of empirical studies within Ekiti State, which this study aims to address. The study employed a descriptive survey design. Data were collected from a random sample of 324 staff, selected from a population of 1715 across the ministries, using validated self-constructed questionnaires. Reliability was confirmed via Cronbach’s alpha (0.80). Data analysis involved descriptive statistics (frequency tables, percentages, mean, standard deviation) for research questions and inferential statistics (chi-square) to test hypotheses at the 0.05 significance level. The results indicated that allowances play a significant role in the job commitment of employees. Furthermore, a strong positive correlation was found between the work environment and employees’ attitudes towards work. It was concluded that both allowances and the working environment are crucial in determining the job commitment and attitude of employees in the ministries. Therefore, it is recommended that the government should review and ensure the prompt payment of all due allowances to motivate employees and enhance their contribution to ministerial operations.